Phytochemistry, toxicity, and acceptability of tawa-tawa (Euphorbia hirta) herbal tea preparations - Trivilegio, Kris Dawn Espela
Euphorbia hirta (tawa-tawa) is widely used as a cure for asthma, hemorrhagic dengue fever, pulmonary illnesses and many other ailments.